Using The Two-Dimensional Transmission Line Modelling Technique To Design Ladder Wave Digital Filters - Abdul Samad, Salina; Hussain, Aini (Malaysian Journal of Computer Science, 1999)
Extends the time domain design approach first introduced for cascaded unit element wave digital filters (WDFs) to ladder WDFs. It shows the correspondence between ladder WDFs and the two-dimensional transmission line networks. The transmission line modelling technique facilitates the design and optimization of ladder WDFs by affording a convenient method of calculating the sensitivities with respect to the design parameters.